1997
DOI: 10.1159/000147926
|View full text |Cite
|
Sign up to set email alerts
|

Altered Kidney Matrix Gene Expression in Early Stages of Experimental Diabetes

Abstract: The expression of mRNA and distribution of α1(IV), α3(IV) chains of type IV collagen, matrix metalloproteinase 2 (MMP-2), and tissue inhibitor of metallo-proteinase 1 (TIMP-1) were examined in kidneys from streptozotocin-diabetic rats, 2.5 months after administration of the drug, an early time point when specific diabetic glomerular changes were still minimal. Ten age-matched Sprague-Dawley rats were assigned to control and diabetic groups. Compared to the controls, the diabetic rats had a significantly lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 4 publications
2
33
0
Order By: Relevance
“…The observed decrease of TIMP-2, specific inhibitor for MMP-2, may represent a balancing cellular effect to decreased MMP levels. Similar observations have been reported for other cell types; increased glucose concentrations resulted in altered expression of matrix, MMPs and TIMPs (Anderson et al, 1996;Kitsiou et al, unpublished data;Leehey et al, 1995), and kidneys of streptozotocindiabetic rats (Wu et al, 1997). Our results indicate that high glucose levels cause changes in HK-2 function, which in turn could contribute to the decreased degradation of the ECM proteins.…”
Section: Karamessinis Et Alsupporting
confidence: 89%
See 1 more Smart Citation
“…The observed decrease of TIMP-2, specific inhibitor for MMP-2, may represent a balancing cellular effect to decreased MMP levels. Similar observations have been reported for other cell types; increased glucose concentrations resulted in altered expression of matrix, MMPs and TIMPs (Anderson et al, 1996;Kitsiou et al, unpublished data;Leehey et al, 1995), and kidneys of streptozotocindiabetic rats (Wu et al, 1997). Our results indicate that high glucose levels cause changes in HK-2 function, which in turn could contribute to the decreased degradation of the ECM proteins.…”
Section: Karamessinis Et Alsupporting
confidence: 89%
“…Studies have demonstrated that high glucose levels in vitro lead to increased expression and accumulation of ECM proteins in different renal cells (Anderson et al, 1996;Ayo et al, 1990Ayo et al, , 1991Danne et al, 1993;Phillips et al, 1997;Roth et al, 1993). Altered matrix expression in kidneys has also been observed in streptozotocin-diabetic rats (Wu et al 1997). In addition, nonenzymatic glycation (NEG) of BM proteins was reported to alter their structure and function in vitro (Anderson et al, 1992(Anderson et al, , 1993Charonis and Tsilibary, 1992;Tsilibary et al, 1988), as well as interactions of these proteins with mesangial, endothelial, and glomerular epithelial cells (Anderson et al, 1994;Haitoglou et al, 1992;Krishnamurti et al, 1997).…”
mentioning
confidence: 99%
“…The reduced synthesis of collagenolytic enzymes by glomerular epithelial cells may be related to the observed thickening of the GBM in diabetic conditions, since turnover of GBM components may be slower than in the normal kidney. In the streptozotocin-diabetic rat model of diabetic nephropathy, reduced expression of collagenase MMP-2 was observed as early as 10 weeks after the onset of diabetes, even before the onset of albuminuria [17]. These results suggest that expression and/or activity of collagenolytic enzymes, in association with hyperglycaemia-induced modulation of integrin expression, may be at least partly responsible for Microvascular basement membranes in diabetes 539 GBM accumulation.…”
Section: Glomerular Basement Membrane (Gbm)mentioning
confidence: 75%
“…Expression of TIMP-2, a specific inhibitor of MMP-2, was strongly increased in glomerular epithelial cells cultured in high glucose [7], and also in situ, in the kidneys of streptozotocin-diabetic rats [17]. Taken together, the above-mentioned data suggests that turnover of basement membrane components may be compromised in diabetic conditions, increased biosynthesis and reduced degradation contributing to matrix accumulation in the GBM.…”
Section: Glomerular Basement Membrane (Gbm)mentioning
confidence: 77%
“…Sprague-Dawley rats were rendered diabetic by an intravenous injection of streptozotocin (STZ), as reported previously (Wu et al, 1997). Seven months after diabetes induction, eight rats (four control, four diabetic) were sacrificed and their kidneys were processed for immunohistochemistry.…”
Section: Immunohistochemistrymentioning
confidence: 99%